2020
DOI: 10.3390/ijerph17103733
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Dioxide Remains a Valid Air Quality Indicator

Abstract: In epidemiological studies, both spatial and temporal variations in nitrogen dioxide (NO2) are a robust predictor of health risks. Compared to particulate matter, the experimental evidence for harmful effects at typical ambient concentrations is less extensive and not as clear for NO2. In the wake of the “Diesel emission scandal—Dieselgate”, the scientific basis of current limit values for ambient NO2 concentrations was attacked by industry lobbyists. It was argued that associations between NO2 levels and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…in volunteers exposed in an exposure chamber [1]. This is particularly true for nitrogen dioxide [2] for which we have also demonstrated short-term effects in previous time series studies in Vienna [3,4]. One explanation of significant effects of the irritant gas in epidemiological studies in the absence of effects in experimental settings would be through an indirect pathway: nitrogen dioxide at typical environmental concentrations would not damage cells of the respiratory epithelium directly but would still increase their susceptibility to other factors including allergens [5] or infectious agents.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…in volunteers exposed in an exposure chamber [1]. This is particularly true for nitrogen dioxide [2] for which we have also demonstrated short-term effects in previous time series studies in Vienna [3,4]. One explanation of significant effects of the irritant gas in epidemiological studies in the absence of effects in experimental settings would be through an indirect pathway: nitrogen dioxide at typical environmental concentrations would not damage cells of the respiratory epithelium directly but would still increase their susceptibility to other factors including allergens [5] or infectious agents.…”
Section: Introductionsupporting
confidence: 74%
“…Based on these findings, we expected an effect of air pollution on COVID-19-related mortality. We have demonstrated significant effects of air pollution on mortality before [3,4] and effect estimates were usually larger the more specific the cause of death. But the more specific the cause of death, the rarer would be the events.…”
Section: Discussionmentioning
confidence: 80%
“…The city of Vienna maintains a dense air quality monitoring network that has been used to examine health impacts of air pollution before [ 18 ]. The density of pollution-monitoring stations allows for an analysis of air pollution effects on COVID-19 infections and deaths on the basis of rather small urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Among these pollutants, NO 2 is notable as increased levels have been seen to affect the distribution of ozone ( Villena et al, 2012 ) and give rise to secondary inorganic aerosol pollutants ( Behera and Sharma, 2011 , Gkatzelis et al, 2021 ). Furthermore, NO 2 and its associated secondary pollutants ( Sokan-Adeaga et al, 2019 ) are respiratory irritants, thus metrics centered around NO 2 have frequently been used as robust indicators of health risks ( Moshammer et al, 2020 ). In fact, many studies have found that air pollutants could increase COVID-19 cases ( Zhu et al, 2020 ) and mortality ( Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%